Newtonian heating effect in pulsating magnetohydrodynamic nanofluid flow through a constricted channel: A numerical study - Ali, Amjad; Bukhari, Zainab; Amjad, Muhammad; Ahmad, Sohail; Tag El. Din, El. Sayed M.; Hussain, Syed M. (Frontiers in Energy Research, 2022)
This article investigates the pulsatile flow of viscous incompressible MHD nanofluid in a rectangular channel. At the upper and lower walls, the channel has symmetrical constrictions. The goal is to analyze the heat transfer features of the nanofluid flow under the effect of the magnetic field and thermal radiation. Five different nanofluids, formed with nanoparticles of copper (Cu), magnetite (Fe3O4), silver (Ag), titanium oxide (TiO2), and single wall carbon nanotube (SWCNT) in the base fluid of water, are considered in the study. The unsteady governing equations are transformed using the vorticity-stream function approach. The solution is obtained using the finite difference technique (FDM). The effect of various flow controlling parameters on velocity, temperature, Nusselt, and skin-friction profiles is inspected by using graphs. Across the channel, graphs of vorticity, streamlines, and temperature distribution are also displayed. The thickness of the thermal boundary layer upsurges with escalating values of the magnetic field, radiation parameters, and solid volume fraction, whereas it declines with escalating values of the Strouhal and Prandtl numbers. The profiles are usually found to have a more regular pattern upstream of the constriction than that downstream of the constriction. At the throat of the constriction, the carbon nanotube-based nanofluid attains higher temperatures than the other nanofluids downstream of the constriction. However, in the lee of the constriction, silver-based nanofluid attains higher temperatures than the other nanofluids downstream of the constriction. The behavior, in most cases, is opposite upstream of the constriction. The findings of the study can be utilized to cure stenosis in blood vessels, design biomechanical devices, and employ flow pulsation to control industrial operations.